Horizontal Gaze Palsy With Progressive Scoliosis and Severe Keratoconus With a Compound Heterozygous Mutation in ROBO3. - Pina, S (2016)
The authors report the case of a child with horizontal gaze palsy with progressive scoliosis and keratoconus. ROBO3 analysis identified compound heterozygous mutations. Keratoconus surgical approach resulted in visual acuity improvement in both eyes. The previously unreported occurrence of keratoconus with horizontal gaze palsy with progressive scoliosis suggests that ophthalmologic assessment should search for signs of this ectasia in these patients.